Wednesday

April 23, 2014

April 23, 2014

Posted by **Bob** on Tuesday, May 22, 2012 at 2:16am.

- Algebra 2 -
**Reiny**, Tuesday, May 22, 2012 at 8:05amfactor first

(3x-2)/((x-3)(x-9)) - (3x-8)/((x-3)(x-6)) + (x+2)/((x-9)(x-6))

so the LCD is ((x-3)(x-6)(x-9)

= [ (3x-2)(x-6) - (3x-8)(x-9) + (x+2)(x-3) ]/[(x-3)(x-6)(x-9)]

= [3x^2 - 20x + 12 - 3x^2 + 35x - 72 + x^2 - x - 6]/[(x-3)(x-6)(x-9)]

= (x^2 + 14x -66)/[(x-3)(x-6)(x-9)]

check my arithmetic

**Related Questions**

algebra,math,help - Use Property 2 to simplify each of the following radical ...

algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...

algebra 2 - find all the zeroes of: x^5-3x^4-24x^3-72x^2-25x+75=0 5x^5-20x^4-40x...

Algebra 1 Part 2 - Simplify the rational expressions.State any excluded values:(...

algebra - Can someone please help me with this math problem? Thanks. Let g(x)=x^...

Algebra - Factor: 3x^2 - 27 3x^2-27=0 27+(3x^2-27)=0+27 3x^2=27 (3x^2)/3=27/3 x^...

algebra - simplify the rational expressions. State any excluded values. 1. 3x-6 ...

Algebra - I'm not sure how to factor 3x^3-12x^2+3x. I tried separatring the 3x ...

Algebra - (3x+4)/(3x-4)+(3x-4)/(3x+4) --------------------------- Divide top by ...

Intermediate Algebra - Andrews factored expressions -6x63+9x^2-3x as -3x(2x^2-3x...